Violence and the Obligations of Charity - Floyd, Shawn (Proceedings of the American Catholic Philosophical Association, 2015)
According to one interpretive strand of the Christian moral tradition, charity requires complete renunciation of violence in all its forms. One should not summarily dismiss this view as extreme or unrepresentative of Christian teaching. After all, sacred Scripture urges us to love our neighbors (including our enemies) and repudiate wanton aggression, hatred, and personal reprisals. Yet while charity would have us disavow all varieties of malicious acts and urges, it is not obvious that it forbids using potentially lethal force. Relying on insights from Aquinas, I argue that charity may not only permit but require such force in order to combat the cruelty and aggression directed at our beloved or those in our care.